A snapshot of the global policies and practices of medicine use reviews by community pharmacist in chronic diseases: a narrative review - Naeem Mubarak; Sarwat Ali Raja; Tahir Mehmood Khan; Che Suraya Zin (Journal of the Pakistan Medical Association, 2020)
Medicine use review is a tool to improve medication adherence and safety. The current narrative review was planned to explore global policies and practices of medicine use review by community pharmacists in chronic diseases, its impact and way forward for low- and middle-income countries. Key words, such as ?medicine use review?, ?medication therapy management? and ?community pharmacy? were used for search on PubMed and CINAHL databases for articles published from 2004 to 2019. Medicine use review has opened an avenue of ongoing collaboration between community pharmacists and general practitioners. High-income countries have witnessed a gradual yet cautious adoption of these services through effective policy shift. In terms of practices and impact, the situation in high-income countries was promising where on an average ?type-II? medicine use review was widely in practice and had improved clinical, humanistic and economic outcomes in chronic disease. However, . Continuous....